The Imperative Character of the Administrative Conflict in Kosovo: Array - Ibraimi, Xhemazie (Acta Universitatis Danubius. Juridica, 2020)
This paper aims to show the importance of the institution of administrative conflict in the true and qualitative protection of the rights and interests of the parties. The control of the legality of certain administrative acts by the judiciary is an indisputable fact that provides not only objective protection, but also subjective protection of the violated rights and interests of the parties. The parties request protection or intervention of the judiciary for the realization of their rights in various areas such as: denationalization, administrative contracts, concession, electoral process, minor offenses, pension rights, disability insurance, customs rights and tax procedures, property rights (eg privatization of construction land, transformation of construction land), and other rights provided by law. This judicial intervention enables the realization of a right violated by the final administrative act. Given the fact that the basic condition for initiating an administrative court procedure or administrative dispute is the existence of a final administrative act, the path to the realization of that right or correction of the wrong is long and complicated. According to the legal provisions in Kosovo, where judicial protection is not realized by specialized administrative courts such as the Administrative Courts of the countries of the region, the legal protection of the subjectively violated norm passes through several institutions as well: before the second instance institution after a complaint in administrative appeal procedure, before the Basic Court (administrative department), before the Court of Appeals and the Supreme Court as the last instance which acts on the basis of extraordinary legal remedies.. Passing through these institutions complicates the realization of the right of the party and does not guarantee the de facto realization of the legal rights of the parties.. As a rule, always after the end of administrative disputes we do not have a meritorious placement of judicial bodies in full jurisdiction, but the "won" case is returned to the administrative authorities and the administrative procedure begins again! To prove what we said above, we will try to answer the following questions: Does the court decision provide a guarantee for the acquisition of a violated right for the party, or return to administrative reconsideration? How is the principle of compulsory court decision applied? How to strike a balance between the decisions made and their execution?